ANALISIS PENGENDALIAN INTERNAL DAN PROFESIONALISME DALAM PENCEGAHAN PENGHINDARAN PAJAK DAN PENIPUAN DI INDONESIA. - Fangela Myas Sari (EKOMBIS: JURNAL FAKULTAS EKONOMI, 2023)
Abstrak  This study aims to analyze internal control and professionalism in preventing tax evasion and fraud.This research is a qualitative research that uses literature review methods from books and previous research.The results obtained through this study indicate that the control system and professionalism are interrelated to prevent tax evasion and fraud because a good control system must be carried out by someone who has a high professionalism attitude so as to prevent tax evasion and fraud.